2022
DOI: 10.3389/fonc.2022.1007538
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and validation of a prognostic nomogram for extrahepatic cholangiocarcinoma

Abstract: Simple summaryAccurately estimate the prognosis of patients with ECCA is important. However, the TNM system has some limitations, such as low accuracy, exclusion of other factors (e.g., age and sex), and poor performance in predicting individual survival risk. In contrast, a nomogram-based clinical model related to a comprehensive analysis of all risk factors is intuitive and straightforward, facilitating the probabilistic analysis of tumor-related risk factors. Simultaneously, a nomogram can also effectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…By the time of follow-up, we found a 3-year cumulative mortality rate of 78.0% and 15.0% for CSS and non-cancer-specific mortality, respectively, indicating a large competitive relationship between CSS and non-cancer-specific mortality. Generally, a higher age is the main reason for a competitive relationship [22] . However, in the present study, increasing age was not significantly associated with OS in patients with advanced ECCA and was more irrelevant in CSS.…”
Section: Css Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…By the time of follow-up, we found a 3-year cumulative mortality rate of 78.0% and 15.0% for CSS and non-cancer-specific mortality, respectively, indicating a large competitive relationship between CSS and non-cancer-specific mortality. Generally, a higher age is the main reason for a competitive relationship [22] . However, in the present study, increasing age was not significantly associated with OS in patients with advanced ECCA and was more irrelevant in CSS.…”
Section: Css Curvesmentioning
confidence: 99%
“…The nomogram facilitates the development of individualized treatment regimens by physicians, offers more precise prognostic predictions, and has been applied to the evaluation of a variety of malignancies such as colorectal cancer,osteosarcoma and lung cancer [32[34] . Prognostic nomogram establishment was carried out in ECCA patients by Fang et al, showed that nomograms are more predictive for patient survival than AJCC staging [22] . As in our study, in comparison to the 7th AJCC stage, the produced nomograms displayed higher time-dependent C-indexes and AUC values, demonstrating their modified discriminative ability to predict OS and CSS.…”
Section: Css Curvesmentioning
confidence: 99%